Effectiveness of an integrated telehealth service for patients with depression: a pragmatic randomised controlled trial of a complex intervention - Salisbury, Chris; O'Cathain, Alicia; Edwards, Louisa; Thomas, Clare; Gaunt, Daisy; Hollinghurst, Sandra; Nicholl, Jon; Large, Shirley; Yardley, Lucy; Lewis, Glyn; Foster, Alexis; Garner, Katy; et al. (The Lancet. Psychiatry, 2016)
Many countries are exploring the potential of telehealth interventions to manage the rising number of people with chronic disorders. However, evidence of the effectiveness of telehealth is ambiguous. Based on an evidence-based conceptual framework, we developed an integrated telehealth service (the Healthlines Service) for chronic disorders and assessed its effectiveness in patients with depression. We aimed to compare the Healthlines Depression Service plus usual care with usual care alone. This study was a pragmatic, multicentre, randomised controlled trial with participants recruited from 43 general practices in three areas of England. To be eligible, participants needed to have access to the internet and email, a Patient Health Questionnaire 9 (PHQ-9) score of at least 10, and a confirmed diagnosis of depression. Participants were individually assigned (1:1) to either the Healthlines Depression Service plus usual care or usual care alone. Random assignment was done by use of a web-based automated randomisation system, stratified by site and minimised by practice and PHQ-9 score. Participants were aware of their allocation, but outcomes were analysed masked. The Healthlines Service consisted of regular telephone calls from non-clinical, trained health advisers who followed standardised scripts generated by interactive software. After an initial assessment and goal-setting telephone call, the advisers called each participant on six occasions over 4 months, and then made up to three more calls at intervals of roughly 2 months to provide reinforcement and to detect relapse. Advisers supported participants in the use of online resources (including computerised cognitive behavioural therapy) and sought to encourage healthier lifestyles, optimise medication, and improve treatment adherence. The primary outcome was the proportion of participants responding to the intervention (defined as PHQ-9 <10 and reduction in PHQ-9 of ≥5 points) at 4 months after randomisation. The primary analysis was based on the intention-to-treat principle without imputation and all serious adverse events were investigated. This trial is registered with Current Controlled Trials, number ISRCTN 14172341. Between July 24, 2012, and July 31, 2013, we recruited 609 participants, randomly assigning 307 to the Healthlines Service plus usual care and 302 to usual care. Primary outcome data were available for 525 (86%) participants. At 4 months, 68 (27%) of 255 individuals in the intervention group had a treatment response compared with 50 (19%) of 270 individuals in the usual care group (adjusted odds ratio 1·7, 95% CI 1·1-2·5, p=0·019). Compared with usual care alone, intervention participants reported improvements in anxiety, better access to support and advice, greater satisfaction with the support they received, and improvements in self-management and health literacy. During the trial, 70 adverse events were reported by participants, one of which was related to the intervention (increased anxiety from discussing depression) and was not serious. This telehealth service based on non-clinically trained health advisers supporting patients in use of internet resources was both acceptable and effective compared with usual care. Our results provide support for the development and assessment of similar interventions in other chronic disorders to expand care provision. National Institute for Health Research (NIHR).